Glycerol-based deep eutectic solvents: Physical properties - AlOmar, M.K.; Hayyan, M.; AlSaadi, M.A.; Akib, S.; Hayyan, A.; Hashim, M.A. (Elsevier, 2016)
Deep eutectic solvents (DESs) have been used in many industrial applications. DES is a mixture of a salt and a hydrogen bond donor (HBD). In this study, 70 DESs were synthesized successfully based on glycerol (Gly) as the HBD with different phosphonium and ammonium salts, namely methyl triphenyl phosphonium bromide (MTPB), benzyl triphenyl phosphonium chloride (BTPC), allyl triphenyl phosphonium bromide (ATPB), choline chloride (ChCl), N,N-diethylethanolammonium chloride (DAC), and tetra-n-butylammonium bromide (TBAB). The DESs were prepared using different molar ratios of the HBD to the salts. The freezing point of each DES was determined using Differential Scanning Calorimetry (DSC). The physical properties of these DESs, including density, viscosity, conductivity, and surface tension, were investigated as functions of temperature. In addition, the functional groups were analyzed utilizing Fourier transform infrared (FTIR) spectroscopy. It is worth noting that these systems have a wide variety of physical properties, which implies that these DESs would be suitable for diverse applications.